COMPLEMENTARY FEEDING INDICATORS FOR CHILDREN AGED 6 TO 23 MONTHS ACCORDING TO BREASTFEEDING STATUS - Leonez,Daniella Garcia Vidal Rodrigues (2021)
ABSTRACT Objective: To verify if there are differences among the complementary feeding indicators of children aged 6-23 months according to the breastfeeding status. Methods: A cross-sectional study was carried out with 1,355 children aged 6-23 months in 2012 to evaluate five indicators proposed by the World Health Organization (WHO) and modified in accordance with Brazilian’s recommendations “Ten steps to a healthy feeding: a feeding guide for children under two years old”. The indicators used were: I. Introduction of solid, semi-solid or soft foods; II. Minimum dietary diversity; III. Minimum meal frequency; IV. Minimum acceptable diet, and V. Consumption of iron-rich foods. To verify differences between the complementary feeding indicators according to breastfeeding status, the F-statistic was used, with p≤0.05 meaning significant. Results: Indicators I, II, and V were similar among breastfed and non-breastfed children; however, indicators III and IV presented a higher proportion of adequacy for non-breastfed children, with 94.9% (CI95% 93.2-96.2) versus 40.3% (CI95% 33.2-47.9) for indicator III, and 57.3% (CI95% 53.2-61.2) versus 23.1% (CI95% 17.4-30.1) for indicator IV. Conclusions: Non-breastfed children have better complementary feeding status, but the indicator III takes into account non-breast milk as a meal for non-breastfed children, which increased the number of dairy meals and influenced indicator IV (calculated from indicators II and III).